Trends in the Evolution of Worldwide Foreign Direct Investments - Maria Ramona Sarbu; Iuliana Mazur (CES Working Papers, 2014)
The flows of foreign direct investments constitutes a major component of the phenomena that manifest themselves in the world economy, these representing financial resources geared toward a particular investment area that allow those who invest to develop operations over which they have the control and the decision-making power. Given the fact that the world economy is characterized by the increasing interconnectedness of national states as a result of spreading the links in the spheres of economic, political, social and cultural life, following starting with 2008 a period of unusual developments, the purpose of the paper is to analyze the evolution of worldwide foreign direct investment (FDI) inflows, before and after the onset of the global economic crisis.
Keywords: F21; 330; foreign direct investment; FDI inflows; financial crisis Romania